The Current Landscape of Congenital Heart Surgery in Northern China: A Geographic and Population-Based Analysis - Su, Zhanhao; Xiang, Li; Liu, Zeye; Wu, Hao; Li, Shoujun; Chen, Huiwen; Zhang, Hao (Frontiers in Pediatrics, 2021)
Background Congenital heart disease (CHD) is the leading birth defect in China and many patients require congenital heart surgery (CHS) to achieve optimal outcomes. However, the current landscape and population accessibility to specialist resources for CHS in China are unclear. Methods Care facilities performing CHS were identified from the 2018 white book of Chinese cardiovascular surgery and were categorized as full or limited facilities based on specialist capacity. Census-based population data and road data were obtained from administrative sources. Service area analysis of all facilities was performed to estimate geographic accessibility. Results Of 93 facilities in 14 provinces and municipalities in north China, only 30.1% had full specialist capacity. The shortage of pediatric cardiologists and mechanical circulatory support was the primary limiting factor. In 2018, 61.3% of facilities performed < 200 cases of CHS, and 31.6% of all CHS (N = 30,921) were performed in limited facilities with substantially lower volume than full-capacity facilities (Median: 85.0 versus 368.0). Beijing had a disproportionately higher CHS volume (367 cases per million population) than other provinces. Of all children under 5 in north China, only 12.9% live within 30 kilometers (typical half‐day visit) of the service areas of all facilities. Compared with children from the eastern region (31.4%), 71.8% and 70.2% of children from central and western regions needed to travel >180 kilometers (typical overnight visit) to receive care in full-capacity facilities. Conclusions Many facilities for CHS in north China had limited specialist capacity and many CHD patients received suboptimal surgical care. Policy measures should address the significant geographic disparities to receive high-quality surgical care among disadvantaged patients.